Extraction of methamphetamine and pseudoephedrine by modified graphene oxide solid phase extraction method coupled to HPLC-UV in urine sample - Nasim Nourani; Yousef Javadzadeh; Ali Shayanfar; Arezou Taghvimi; Ahad Bavili-Tabrizi; Siavoush Dastmalchi (BMC Chemistry)
Abstract Methamphetamine, pseudoephedrine, and related drugs are among the first drugs used for the stimulation of the central nervous system. In this study, two adsorbents based on graphene oxide (GO) were synthesized and used for the analysis of methamphetamine and pseudoephedrine. The prepared nano-adsorbents based on GO in this study were coated by polyaniline (PANI) and Fe3O4/C-nanodot/GO (magnetic adsorbent). The average size of nanoparticles (GO/PANI) was 18.43 nm. The specific surface area and pore size diameter of Fe3O4/C-nanodot/GO were 22.71 m2 g− 1 and 15.23 nm, respectively. Experimental variables affecting the extraction efficiency of the analytes such as pH of the sample solution, amount of adsorbent, extraction time, and type of eluents were investigated and optimized by response surface methodology. Under optimum conditions, GO/PANI and Fe3O4/C-nanodot/GO were considered appropriate solid phase extraction adsorbents for HPLC-based analyses of the studied drugs in human urine samples. However, GO/Fe3O4 nano adsorbent (Fe3O4/C-nanodot/GO) showed superior working condition than GO/PANI. The validated proposed analytical methods can be used for the quantitative determination of methamphetamine and pseudoephedrine in actual samples.